Social policy and the ethic of care - Hankivsky, Olena (UBC Press, 2004)
"In this book, Hankivsky considers the implications of this ethic for a range of Canadian social policy issues. Through a series of case studies, she demonstrates the extent to which a care orientation differs from a justice orientation, and provides an alternative normative framework for interpreting, understanding, and evaluating social policy. She reveals why Canadian social policy is lacking and how it could be made more effective and robust by the inclusion of an ethic of care."--Jacket